PENATAAN SISTEM SUNGAI SENGKARANG SEBAGAI SALAH SATU PENANGANAN ROB KOTA/ KABUPATEN PEKALONGAN - Muhammad Firqotul Ulum; Aji Perdana Wira Utama; Suripin Suripin; Sumbogo Pranoto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Tidal flood which’s occured at Pekalongan City/District entered into settlement through a river that empties into the sea, beach and drainage. This condition will be critical when at the same time the highest tides and great flood. Tidal flood is predicted to increase due to rising sea levels ranged from 4,46 to 4,60 mm/year and there’s land subsidence about 3 cm/year. Tidal flood which’s enter into settlements with the river one of them occurred at Sengkarang river system (Sengkarang river, Meduri river and Bremi river). The occurrence of runoff in rivers such as the capacity of the river current is smaller than the existing discharge. To overcome this, the rivers will be evaluated its capacity to discharge plans return period of 25 years (Q25) which is accompanied by tidal conditions. Analysis is needed to evaluate the capacity of the river including hydrological, tidal and hydraulic analysis. Hydrological analysis is used to calculate the flood discharge plan with the HSS Gama 1 method. Tidal analysis is used to determine the height of the sea surface elevation. Hydraulic analysis is used to calculate the capacity and dimensions of the river using HEC-RAS 4.1 software. HEC-RAS simulation performed with two scenarios. The first scenario is the merge of the downstream of Meduri river and Bremi river with Sengkarang river. The second scenario is the separate of the downstream of Meduri river and Bremi river with Sengkarang river. Results from HEC-RAS simulation with discharge plans Q25 and tidal conditions/HHWL for existing cross-section of the river showed that hydraulically separated model is more profitable than merge model because the water level in separated scenario is lower than the merge scenario and estimated from sedimentation will better because its estuary has been separated.